2020
DOI: 10.1177/0886260520922514
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Intimate Partner Violence Exposure and Autonomic Reactivity: Associations With Positive Parenting

Abstract: Intimate partner violence (IPV) can negatively impact parenting, posing a threat both to the wellbeing of mothers and their young children. Parenting may also be influenced by emotion regulation (ER), which can support parents’ ability to navigate relational challenges or buffer against the influence of adverse experiences on parenting. Changes in maternal respiratory sinus arrhythmia (RSA) during parent–child interactions have been conceptualized as a psychophysiological index of ER. Competing theoretical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Thus, in moments when preschool-aged children show minor increases in frustration or disappointment, maintaining stability in one’s RSA or vagal augmentation may help mothers respond with greater emotional support. This interpretation is consistent with studies showing that maternal vagal augmentation is associated with more supportive caregiving behaviors during moderate interactive challenges with toddler- and preschool-aged children (Giuliano et al, 2015; Lorber & O’leary, 2005; Lorber et al, 2016; Molina et al, 2020; but see Skowron et al, 2013, for an exception). Notably, by examining within-person associations between these constructs, we extend prior research that has predominantly examined individual differences in maternal parasympathetic physiology.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, in moments when preschool-aged children show minor increases in frustration or disappointment, maintaining stability in one’s RSA or vagal augmentation may help mothers respond with greater emotional support. This interpretation is consistent with studies showing that maternal vagal augmentation is associated with more supportive caregiving behaviors during moderate interactive challenges with toddler- and preschool-aged children (Giuliano et al, 2015; Lorber & O’leary, 2005; Lorber et al, 2016; Molina et al, 2020; but see Skowron et al, 2013, for an exception). Notably, by examining within-person associations between these constructs, we extend prior research that has predominantly examined individual differences in maternal parasympathetic physiology.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence also suggests that vagal augmentation is associated with greater parental support (or less nonsupport) during parent–child interactions. For instance, mothers who displayed vagal augmentation relative to baseline during moderately challenging tasks with their toddler- and preschool-aged children were rated higher on warm, positive parenting behaviors and coordination with their children, and lower on harsh discipline practices during the interaction (Giuliano et al, 2015; Lorber et al, 2016; Lorber & O’leary, 2005; Molina et al, 2020). Other work has illustrated that mothers tend to show vagal augmentation while watching positively or negatively evocative film clips with their children, yet less so when watching similar clips alone.…”
Section: Maternal Emotional Support and Respiratory Sinus Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…ANS reactivity may be particularly relevant to understanding parenting behaviors in the moment, in that excessive or blunted reactivity may be barriers to responding effectively to infant cues. Indeed, recent work has linked RSA activity during parenting tasks to parenting quality and behaviors among low-income mothers of preschool-aged children (Molina et al, 2022;Skowron et al, 2013). In one study of pregnant women, Lin et al (2019) found that emotion dysregulation corresponded to blunted RSA reactivity to an infant cry task in a sample of pregnant women (26-40 weeks gestation).…”
Section: Maternal Autonomic Nervous System Regulation and Parentingmentioning
confidence: 99%